2020
DOI: 10.1186/s13287-020-01742-3
|View full text |Cite
|
Sign up to set email alerts
|

Pax7 as molecular switch regulating early and advanced stages of myogenic mouse ESC differentiation in teratomas

Abstract: Background: Pluripotent stem cells present the ability to self-renew and undergo differentiation into any cell type building an organism. Importantly, a lot of evidence on embryonic stem cell (ESC) differentiation comes from in vitro studies. However, ESCs cultured in vitro do not necessarily behave as cells differentiating in vivo. For this reason, we used teratomas to study early and advanced stages of in vivo ESC myogenic differentiation and the role of Pax7 in this process. Pax7 transcription factor plays … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 87 publications
2
21
0
Order By: Relevance
“…The first striking observation was that even after 3 days in differentiation media, NRMT1 knockout (KO) C2C12 cells lacked expression of the master regulator of postnatal myogenesis, Pax7 (Figure 5(b)). The transcription factor Pax7 and its paralog Pax3 regulate myogenic precursor cell differentiation through their downstream targets, the myogenic regulatory factors, which include myogenic factor 5 (Myf5), myogenic differentiation 1 (MyoD), muscle-specific regulatory factor 4 (Myf4), and myogenin (MyoG) 51 . Accordingly, MyoG expression was also minimally expressed over the differentiation period (Figure 5 progenitor pool that can also give rise to osteoblasts, adipocytes, and chondrocytes 52 .…”
Section: Effect Of Nrmt1 Loss On Muscle Cell Differentiationmentioning
confidence: 99%
“…The first striking observation was that even after 3 days in differentiation media, NRMT1 knockout (KO) C2C12 cells lacked expression of the master regulator of postnatal myogenesis, Pax7 (Figure 5(b)). The transcription factor Pax7 and its paralog Pax3 regulate myogenic precursor cell differentiation through their downstream targets, the myogenic regulatory factors, which include myogenic factor 5 (Myf5), myogenic differentiation 1 (MyoD), muscle-specific regulatory factor 4 (Myf4), and myogenin (MyoG) 51 . Accordingly, MyoG expression was also minimally expressed over the differentiation period (Figure 5 progenitor pool that can also give rise to osteoblasts, adipocytes, and chondrocytes 52 .…”
Section: Effect Of Nrmt1 Loss On Muscle Cell Differentiationmentioning
confidence: 99%
“…It has been reported that Pax7 expression is crucial for the maintenance and self-renewal of myoblasts (19,20). Maintaining Pax7 expression retains the transcriptional regulation of Pax7 for myogenesis and for downregulation at the onset of muscle differentiation (21,22).…”
Section: Golgi Matrix Protein-130kda (Gm130): Golgimentioning
confidence: 99%
“…Many studies validated this model as a tool to test pluripotency of mouse [ 17 , 18 ] or human cells [ 19 , 20 , 21 ], including first iPSCs derived (e.g., [ 22 , 23 ]). It was also applied to study genetically modified PSCs (e.g., [ 24 , 25 ]).…”
Section: Introductionmentioning
confidence: 99%
“…In mice, ablation of this factor leads to early postnatal lethality [ 26 ]. Lack of the functional PAX7, however, does not prevent myogenesis but affects its progression ([ 4 , 25 , 27 , 28 ]). Importantly, in Pax7 -null mice the number of muscle-specific stem cells, i.e., satellite cells (SCs), is lower in skeletal muscles [ 29 , 30 ] and tunica muscularis of the esophagus [ 31 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation